2022
DOI: 10.3390/molecules27206924
|View full text |Cite
|
Sign up to set email alerts
|

Delta-8 Tetrahydrocannabinol Product Impurities

Abstract: Due to increased concerns regarding unidentified impurities in delta-8 tetrahydrocannabinol (Δ-8 THC) consumer products, a study using Nuclear Magnetic Resonance (NMR), high performance liquid chromatography (HPLC), and mass spectrometry (MS) was conducted to further investigate these products. Ten Δ-8 THC products, including distillates and ready to use vaporizer cartridges, were analyzed. The results yield findings that the tested products contain several impurities in concentrations far beyond what is decla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…149,150 Additional impurities may originate from plant-derived minor cannabinoids, such as cannabidivarin, cannabidihexol, or tetrahydrocannabihexol, carried over from the hemp plant during extraction. 135,151 Interestingly, some analytical certificates posted on the Internet for HHC products reported non-hydrogenated cannabinoids, such as CBD, CBG, and CBGA as minor components. 152 HHC is often sold in vaping products.…”
Section: Potential Contaminants In Hhc Preparationsmentioning
confidence: 99%
“…149,150 Additional impurities may originate from plant-derived minor cannabinoids, such as cannabidivarin, cannabidihexol, or tetrahydrocannabihexol, carried over from the hemp plant during extraction. 135,151 Interestingly, some analytical certificates posted on the Internet for HHC products reported non-hydrogenated cannabinoids, such as CBD, CBG, and CBGA as minor components. 152 HHC is often sold in vaping products.…”
Section: Potential Contaminants In Hhc Preparationsmentioning
confidence: 99%
“…Ray et al (2022) used 1 H-NMR, HPLC-UV, and HPLC-MS to determine unknown impurities in Δ 8 -THC consumer products purchased online or from local retailers from the USA [ 66 ]. Ten Δ 8 -THC products, including distillates and vaporizers, were analyzed during the study.…”
Section: Analysis Of δ 8 -Thcmentioning
confidence: 99%
“…The identified compounds included cannabidivarin (CBDV) and cannabidihexol (CBDH). The study concluded that the problem with these products is threefold: impure CBD starting material, poor post-reaction purification, and inadequate separation of closely related cannabinoids during laboratory analysis of the final product [ 66 ].…”
Section: Analysis Of δ 8 -Thcmentioning
confidence: 99%
“…Because the methods used to convert CBD to Δ 8 -THC are not specifically addressed in hemp laws, the legality of synthetic Δ 8 -THC stays unclear. This raises safety and product quality concerns for consumers given the unknown and untested nature of Δ 8 -THC, other synthetic analogs, and any other impurities present 24 , 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Because the methods used to convert CBD to Δ 8 -THC are not specifically addressed in hemp laws, the legality of synthetic Δ 8 -THC stays unclear. This raises safety and product quality concerns for consum-ABBREVIATIONS 4,8-epoxy-iso-THC 4,8-epoxy-iso-tetrahydrocannabinol 8-OH-iso-THC United States Pharmacopeia Δ 4,8 -iso-THC Δ 4,8 -iso-tetrahydrocannabinol Δ 4 -iso-THC Δ 4 -iso-tetrahydrocannabinol Δ 8 -cis-iso-THC Δ 8 -cis-iso-tetrahydrocannabinol Δ 8 -iso-THC Δ 8 -iso-tetrahydrocannabinol Δ 8 -THC trans-Δ 8 -tetrahydrocannabinol Δ 9 -THC trans-Δ 9 -tetrahydrocannabinol ers given the unknown and untested nature of Δ 8 -THC, other synthetic analogs, and any other impurities present [24][25][26]. U. S. health officials are warning about the potential dangers of Δ 8 -THC following hospitalizations tied to the substance.…”
mentioning
confidence: 99%